PENGARUH KUALITAS PENGUNGKAPAN INFORMASI DAN PENERAPAN CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN DI BURSA EFEK INDONESIA - Mita Hapsari, 07.05.52.0080; Nurhayati, Ida (Students Journal of Accounting and Banking, 2015)
This study aimed to examine the association of corporate governance applied in an enterprise with the companys performance and prove the effect of mandatory disclosure and timeliness of delivery of information on the performance of the company. Based on the index developed using certain criteria by the Indonesian Institute for Corporate Governance, conducted tests on the companys performance against 52 companies that the research samples. This research was conducted using purposive sampling method to non-financial companies who participated in the Corporate Governance Perception Index (CGPI), listed on the Stock Exchange and analyzed using regression analysis. The results showed that the influence of corporate governance proxy for asset mix, the chance to grow and the size of the company as well as mandatory disclosure and timeliness of delivery of information on the performance of the company.Keywords: Corporate Governance, Corporate Performance, Mandatory Disclosure, Timeliness of Information Delivery